THE INFLUENCE OF LIKERS AND VIEWERS ON ONLINE SHOP PRODUCT REVIEW IN INSTAGRAM - Kangiden, Tri Sutrisno (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Online Social networking websites are very popular and  become a part of life, many firm sees this as an opportunity to target new media  for marketing. The purpose of this research is to find the reasons of using Instagram platform for marketing. The research is conducted from users as well organizations through online survey of  instagram. This research is causal type research uses quantitative method which is using questionnaire as a tool to gather data and analysis. The study is conducted through Instagram and will be implemented on Review product. The results showed a linear relationship in the Multiple Regression model, in the other words all the variables affecting consumer preferences simultaneously. Partial test results showed that variables such as Likers, most have a very significant influence. The marketers used instagram in their marketing process by posting the product review and considering about the importance of Likers influences in advanced to see people's interest. The owner of online shop must also evaluate other important factors that affect the consumer preference, regarding with the continuity of business in the future.   Keywords: marketing, online shop, likers, viewers